Effect of injection conditions on the efficiency of intrafollicular immature oocyte transfer (IFIOT) - Chaves Vall Nicolás, Ana Caroline; Costa de Faria, Otávio Augusto; Sant Ana Borges, Marcelo [UNESP]; Ribeiro Kussano, Nayara; Pivato, Ivo; Martins, Carlos Frederico; Warmling Sprícigo, José Felipe; Alves Nunes Dode, Margot (Elsevier, 2025)
We investigated whether injection conditions affect the efficiency of intrafollicular immature oocyte transfer (IFIOT). Four types of needles (27G Gingival, 27G WTA, 27G Spinal, and 30G Gingival), two volumes of phosphate-buffered saline (PBS, 10 and 20 μL), and two quantities (25 and 50) of cumulus-oocyte complexes (COCs) were tested using slaughterhouse ovaries. COCs were injected into follicles ≥10 mm and aspirated. Resistance during injection, reflux, and retention of COCs in the system, as well as recovery and denudation rates were evaluated. Based on these in vitro tests, the 27G Spinal needle with 10 μL were selected for in vivo evaluation using 25 (T25) or 50 (T50) COCs. Simultaneously, groups of 25-30 COCs were used for in vitro embryo production (IVP). After 9 days, uterine flushing was performed, and the diameter and cell number of the embryos produced via IFIOT and IVP were determined. The 10-μL volume was then compared with the previously used 60-μL volume. Data were analyzed using analysis of variance. The recovery rates of the structures and embryos were not affected (P > 0.05) by the quantity of COCs or the quality of injection. However, the 60-μL volume resulted in higher recovery rates of structures than did the 10-μL volume (P ≤ 0.05). The IFIOT and IVP embryos showed similar diameters and cell numbers (P > 0.05). We conclude that the 27G Spinal needle with a volume of approximately 60 μL is the most recommended for IFIOT.